Risk factors, clinical correlates, and social functions of Chinese schizophrenia patients with drug-induced parkinsonism: A cross-sectional analysis of a multicenter, observational, real-world, prospective cohort study - Weng, Jiajun; Zhang, Lei; Yu, Wenjuan; Zhao, Nan; Zhu, Binggen; Ye, Chengyu; Zhang, Zhanxing; Ma, Changlin; Li, Yan; Yu, Yiming; Li, Huafang (Frontiers in Pharmacology, 2023)
Background: Drug-induced parkinsonism (DIP) is the most prevalent neurological side effect of antipsychotics in the Chinese population. Early prevention, recognition, and treatment of DIP are important for the improvement of treatment outcomes and medication adherence of schizophrenia patients. However, the risk factors of DIP and the impact on the clinical syndromes of schizophrenia remain unknown. Aim: The goal of this study was to explore the risk factors, clinical correlates, and social functions of DIP in Chinese schizophrenia patients. Methods: A cross-sectional analysis of a multicenter, observational, real-world, prospective cohort study of the Chinese schizophrenia population with a baseline assessment was conducted from the year 2012 to 2018. Participants were recruited from four mental health centers in Shanghai and totaled 969 subjects. Sociodemographic data, drug treatment, and clinical variables were compared between the DIP group and the non-DIP group. Variables that correlated with the induction of DIP, and with p≤ 0.1, were included in the binary logistic model for analyzing the risk factors of DIP. First generation antipsychotics (FGA)/second generation antipsychotics (SGA) model and high and low/medium D2 receptor antipsychotics were analyzed respectively to control the bias of co-linearity. All risk factors derived from the a forementioned models and clinical variables with p≤ 0.1 were included in the multivariate analysis of clinical correlates and social function of DIP patients. The Positive and Negative Syndrome Scale (PANSS) model and the personal and social performance (PSP) model were analyzed separately to control for co-linearity bias. Results: Age (OR = 1.03, p< 0.001), high D2 receptor antagonist antipsychotic dose (OR = 1.08, p = 0.032), and valproate dose (OR = 1.01, p = 0.001) were the risk factors of DIP. FGA doses were not a significant contributor to the induction of DIP. Psychiatric symptoms, including more severe negative symptoms (OR = 1.09, p< 0.001), lower cognition status (OR = 1.08, p = 0.033), and lower excited symptoms (OR = 0.91, p = 0.002), were significantly correlated with DIP induction. Social dysfunction, including reduction in socially useful activities (OR = 1.27, p = 0.004), lower self-care capabilities (OR = 1.53, p< 0.001), and milder disturbing and aggressive behavior (OR = 0.65, p< 0.001), were significantly correlated with induction of DIP. Valproate dose was significantly correlated with social dysfunction (OR = 1.01, p = 0.001) and psychiatric symptoms (OR = 1.01, p = 0.004) of DIP patients. Age may be a profound factor that affects not only the induction of DIP but also the severity of psychiatric symptoms (OR = 1.02, p< 0.001) and social functions (OR = 1.02, p< 0.001) of schizophrenia patients with DIP. Conclusion: Age, high D2 receptor antagonist antipsychotic dose, and valproate dose are risk factors for DIP, and DIP is significantly correlated with psychiatric symptoms and social performance of Chinese schizophrenia patients. The rational application or discontinuation of valproate is necessary. Old age is related to psychotic symptoms and social adaption in Chinese schizophrenic patients, and early intervention and treatment of DIP can improve the prognosis and social performance of schizophrenia patients. Clinical Trial Registration: Identifier: NCT02640911